Power Transient in a CANDU Reactor - Bertachas, Yiannis (My University, 1978)
In this report, the effectiveness of a proposed Shutoff Rod System a CANDU Reactor was investigated. A full core simulation was done, to study the neutronic power transient following a change in coolant conditions.
This file is officially titled as a project. This is Part B in connection with another project by the same author, titled "Part A: Adjuster Rod Design in a CANDU Reactor and Flux Distributions Due to an Arbitrary Source of Neutrons."http://hdl.handle.net/11375/15387
Keywords: effectiveness; Shutoff Rod System; CANDU Reactor; full core simulation